Mediating cultural memory in Britain and Ireland from the 1688 revolution to the 1745 Jacobite rising - Davis, Leith 1960- (Cambridge University Press, 2022)
Mediating Cultural Memory is the first book to analyze the relationship between cultural memory, national identity and the changing media ecology in early eighteenth-century Britain. Leith Davis focuses on five pivotal episodes in the histories of England, Scotland and Ireland: the 1688 'Glorious' Revolution; the War of the Two Kings in Ireland (1688-91); the Scottish colonial enterprise in Darien (1695-1700); the 1715 Jacobite Rising; and the 1745 Jacobite Rising. She explores the initial inscription of these episodes in forms such as ballads, official documents, manuscript newsletters, correspondence, newspapers and popular histories, and examines how counter-memories of these events continued to circulate in later mediations. Bringing together Memory Studies, Book History and British Studies, Mediating Cultural Memory offers a new interpretation of the early eighteenth century as a crucial stage in the development of cultural memory and illuminates the processes of remembrance and forgetting that have shaped the nation of Britain
Title from publisher's bibliographic system (viewed on 11 Mar 2022)
Of Documents and Declarations: Mediating the 1688 Revolution -- Remembering to Forget: Ireland, The War of the Two Kings and Cultural Amnesia -- National Correspondences: Print, Letters and the Company of Scotland's Darien Expedition -- Writing the 1715 Jacobite Rising: Periodical Networks and the Inscription of News -- Reading the 1745 Jacobite Rising: "Transitory News-papers," "Fleeting Pamphlets" and Knots of Cultural Memory -- Conclusion: "Living On" After 1745: From Cultural Memory to the Memory of Culture
Keywords: Collective memory / Great Britain / History / 18th century; National characteristics, British; Nationalism / Great Britain / History / 18th century; English prose literature / 18th century / History and criticism; Collective memory in literature; Politics and literature / Great Britain / History / 18th century; Printing / Political aspects / Great Britain / History / 18th century